Investigation of heavy metal ions adsorption behavior of silica-supported Schiff base ligands. Issue 56 (1st December 2016) - Koorepazan Moftakhar, Mahdieh; Dousti, Zohreh; Yaftian, Mohammad Reza; Ghorbanloo, Massomeh
Abstract: Schiff base-modified silica gel particles have been shown to be selective and efficient adsorbents for heavy metal ions Cu(II) and Pb(II). This potential was examined as a function of various parameters influencing the adsorption process. The adsorbents were able to be used for multiple adsorption–desorption processes. The analysis of temperature dependency of the process revealed that the adsorption of ions is controlled by positive entropy changes. The isotherm of adsorption process was studied using various models including Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich isotherms. Kinetics data were described by pseudo-second-order model, which allowed suggesting a chemisorption mechanism for the adsorption processes.